Effect of graphene flake size on functionalisation: quantifying reaction extent and imaging locus with single Pt atom tags. Issue 44 (5th November 2021) - Rubio, Noelia; Au, Heather; Coulter, Gabriel O.; Guetaz, Laure; Gebel, Gerard; Mattevi, Cecilia; Shaffer, Milo S. P.
Abstract : The flake size and morphology of the starting material strongly effect the degree and location of grafting when using reductive functionalisation. Abstract : Here, the locus of functionalisation on graphene-related materials and the progress of the reaction is shown to depend strongly on the starting feedstock. Five characteristically different graphite sources were exfoliated and functionalized using a non-destructive chemical reduction method. These archetypical examples were compared via a model reaction, grafting dodecyl addends, evaluated with TGA-MS, XPS and Raman data. A general increase in grafting ratio (ranging from 1.1 wt% up to 25 wt%) and an improvement in grafting stoichiometry (C/R) were observed as flake radius decreased. Raman spectrum imaging of the functionalised natural flake graphite identified that grafting is directed towards flake edges. This behaviour was further corroborated, at atomistic resolution, by functionalising the graphene layers with bipyridine groups able to complex single platinum atoms. The distribution of these groups was then directly imaged using aberration-corrected HAADF-STEM. Platinum atoms were found to be homogeneously distributed across smaller graphenes; in contrast, a more heterogeneous distribution, with a predominance of edge grafting was observed for larger graphites. These observations show that grafting is directed towards flake edges, but not necessary at edge sites; the mechanism is attributed to the relative inaccessibility of the inner basal plane to reactive moieties, resulting in kinetically driven grafting nearer flake edges. This phenomenology may be relevant to a wide range of reactions on graphenes and other 2d materials.